2023
DOI: 10.1038/s41598-023-33990-7
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound-Promoted preparation and application of novel bifunctional core/shell Fe3O4@SiO2@PTS-APG as a robust catalyst in the expeditious synthesis of Hantzsch esters

Abstract: In this work, D-(–)-α-phenylglycine (APG)-functionalized magnetic nanocatalyst (Fe3O4@SiO2@PTS-APG) was designed and successfully prepared in order to implement the principles of green chemistry for the synthesis of polyhydroquinoline (PHQ) and 1,4-dihydropyridine (1,4-DHP) derivatives under ultrasonic irradiation in EtOH. After preparing of the nanocatalyst, its structure was confirmed by different spectroscopic methods or techniques including Fourier transform infrared (FTIR) spectroscopy, energy-dispersive … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 117 publications
0
2
0
Order By: Relevance
“…In this research and in continuing our previous works 29,30,40 , we have reported a novel sustainable green nanomagnetic catalytic system (CS-EDTA-MET@Fe 3 O 4 catalyst, 1) based on modi ed naturally-occurring biopolymeric chitosan, by using methionine amino acid through grafting of EDTA dianhydride linker followed by Fe 3 O 4 decoration. The catalyst (1) was examined in both 3-and 4-components reactions for successful synthesis of corresponding imidazole derivatives in high to excellent yields and short reaction time (Fig.…”
Section: Introductionmentioning
confidence: 66%
See 1 more Smart Citation
“…In this research and in continuing our previous works 29,30,40 , we have reported a novel sustainable green nanomagnetic catalytic system (CS-EDTA-MET@Fe 3 O 4 catalyst, 1) based on modi ed naturally-occurring biopolymeric chitosan, by using methionine amino acid through grafting of EDTA dianhydride linker followed by Fe 3 O 4 decoration. The catalyst (1) was examined in both 3-and 4-components reactions for successful synthesis of corresponding imidazole derivatives in high to excellent yields and short reaction time (Fig.…”
Section: Introductionmentioning
confidence: 66%
“…All these criteria make the processes greener and more sustainable, especially for atom-/step economic multicomponent reactions (MCRs) 28,31,[33][34][35][36] . Nowadays, MCRs are effective tools and procedures to prepare complex scaffolds, which are important in the ne chemical industry including pharmaceutical, dyes and color industries, etc [37][38][39][40][41][42] .…”
Section: Introductionmentioning
confidence: 99%
“…11–15 These catalysts offer advantages such as enhanced catalyst recovery, recyclability, and improved reaction kinetics. 15–18 Compared to traditional catalysts, heterogeneous magnetic catalysts simplify catalyst recovery, reduce costs, and minimize environmental impact. 19,20 Additionally, their recyclability ensures long-term viability and economic feasibility, making them an attractive option in catalysis applications.…”
Section: Introductionmentioning
confidence: 99%
“…These nanocatalysts are used in military, medical, and pharmaceutical industries, oil extraction, and water or soil treatment 1 3 . One of the reasons for the widespread use of iron oxide nanocatalysts is their magnetic properties 4 , 5 Due to the properties of nanocatalysts, more attention has been paid to these materials 6 9 . The synthesis and preparation of nanocatalysts affect their properties, such as chemical composition, morphology, and particle size, and play an essential role in applying nanocatalysts in various engineering industries.…”
Section: Introductionmentioning
confidence: 99%